Dinasti Politik Dalam Pemerintahan Desa di Desa Kancilan Kecamatan Kembang Kabupaten Jepara Periode 1989-2017 (Analisis Implikasi Sosial dan Politik) - Rajiv Windi Tristana; Fitriyah .; Priyatno H (Journal of Politic and Government Studies, 2017)
ABSTRACT Political dynasties can be interpreted as a power practice where family members (family Araceae) given or fixed in the sruktur power of Government so that power is only distributed among relatives, the family of blood. The village which is the smallest Government Unit also did not escape from the existence of a political dynasty. Therefore this research was conducted aiming to know political dynasty in the reign of village in Kancilan Village Kembang Subdistrict of Jepara District. In addition to knowing political dynasty, the study also to know the social and political implications of the existence of a political dynasty. This research uses qualitative research methods, descriptive with documentation and interviewing as a technique of data collection. The subject in this study are purposif. The target in this research is the head of the village of Whistler that did political dynasty, privileged residents, community leaders, as well as communities in the Kancilan Village Kembang Subdistrict of Jepara District.The results of this research show that there's actually a political dynasty in Kancilan Village Kembang Subdistrict of Jepara District for 26 years. The relationship of ruler and privileged residents greatly influences the length of this dynasty existed. Reciprocal relationships between rulers (patron) and society (the client) mutual benefit make this dynasty still exists today. But not always the political dynasty that detriment, itlooks in the village of Kancilan Village that still today families with Officials before. So many positive things that looks first at the village development program because the program always running and gettingbetter. Society tends to receive not even questioned about the political dynasty. Though many felt positive political dynasty, nonetheless there is a negative side that always beware.Keywords: Political Dynasty, Patron-client, Implications.1. PENDAHULUAN